Early prescription of quadruple therapy in acute decompensated heart failure with reduced ejection fraction: A propensity score‐matched analysis - Luis E. Echeverría; Lyda Z. Rojas; Angie Yarlady Serrano‐García; Daniel Botero; Karen Andrea García‐Rueda; Ángela Torres‐Bustamante; Diana Ivonne Cañón‐Gómez; Juan Sebastián Salcedo; Alexandra Hurtado‐Ortiz; Jaime A. Rodríguez; Sergio A. Gómez‐Ochoa (ESC Heart Failure, 2025)
Abstract Aims The optimal timing for prescribing guideline‐directed medical therapy (GDMT) in patients with heart failure with reduced ejection fraction (HFrEF) during acute decompensated heart failure (ADHF) remains uncertain. This study evaluated the real‐world impact of early in‐hospital quadruple GDMT prescription in ADHF patients with HFrEF. Methods and Results In this retrospective cohort study using the Institutional aCute descompensAted heaRt failUre regiStry (ICARUS), we analysed 2051 HFrEF patients (71% male, median age 68 years) hospitalized for ADHF between June 2022 and March 2024. Early quadruple therapy was defined as the prescription of beta‐blockers, angiotensin‐converting enzyme inhibitors (ACEIs)/angiotensin receptor blockers (ARBs)/angiotensin receptor–neprilysin inhibitors (ARNIs), mineralocorticoid receptor antagonists (MRAs) and sodium–glucose cotransporter‐2 inhibitors (SGLT2is) within 48 h of admission. Among included patients, 898 (43.8%) received early quadruple therapy. Using optimal full matching propensity score methodology, early quadruple therapy was associated with lower 30 day mortality/rehospitalization [relative risk (RR) 0.73; 95% confidence interval (CI) 0.55–0.97, P = 0.028], reduced in‐hospital mortality (RR 0.29; 95% CI 0.15–0.56, P < 0.001) and shorter hospital stay (β = −2.65 days; 95% CI −3.67 to −1.63, P < 0.001). Patients receiving early quadruple therapy showed higher rates of GDMT continuation at discharge (RR 3.82; 95% CI 3.01–4.86, P < 0.001). Conclusions In this HFrEF cohort, early initiation of comprehensive GDMT during ADHF hospitalization was associated with improved clinical outcomes. Future randomized trials including patients across the full spectrum of ejection fraction are needed to validate these findings and determine their applicability to other heart failure phenotypes.